Shopping Orientation and Self-Congruence in Shaping Emotional Brand Attachment Among Uniqlo customers in Indonesia - Nursyamsi, Yusriyah Amelia; Rufaidah, Popy (Dinasti Publisher, 2025)
This study analyzes the impact of shopping habits and brand attachment on brand liking among Indonesian Uniqlo customers. The study utilized quantitative data gathered by 220 respondents who do have purchased or used Uniqlo products. The outcomes, fulfilled through Partial Least Squares Structural Equation Modeling (PLS-SEM), draw that customers exhibiting strong task-oriented and experiential shopping orientations tend to form deeper emotional bonds by Uniqlo, as their shopping occasions align closely by their expectations and preferences. Furthermore, when customers perceive a strong congruence among the brand and their actual self, ideal self, social self, or ideal social self, they occasion heightened keepings of pride, correlation, and loyalty toward the brand. The R-squared of 0.800 draws that these issues describe 80% of the variance in emotional brand attachment. These findings handle fill some gaps in earlier studies, that rarely looked at these issues together, especially inside of Indonesia’s fashion market. The study draws that Uniqlo could boost customer loyalty by creating shopping occasions and messages that connect by how customers shop and how they see themselves. Overall, this study offers useful ideas both for theory and for real-world fashion brands working in emerging markets.